Зміни чисельності російськомовних українців в Україні (за матеріалами переписів населення 1989–2001 рр.) - Скляр, В. (Народна творчість та етнографія, 2007)
The author investigates the changes of the number of Russian-speaking Ukrainians on the eve and in the first decade of the Ukrainian independence on the analysis of 1989–2001 census. Taking into account the regional differences of the directions of these changes on the background of the numeral dynamics of all population, ethnic Ukrainians and ethnic Russians are determined.